(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The main aim of the Present investigation was to Studythe mental health and marital Satisfaction among Working Women. The sample wasconsisted of 180 married working women belonging to 60 teachers (30 urban and30 rural), 60 doctors (30 urban and 30 rural),60 administrators (30 urban and30 rural). An incidental purposive sampling technique was used for data collection.The age range of sample is from 25 to 45 years. The participants selected fromurban and rural areas of North Gujarat. Mental health check list by Pramod kumarand marital satisfaction scale by Brinda Amritraj and Jay Prakash were used. Toanalyzed the data ‘t’ test was used. The results clearly indicate thatsignificant differences existed between urban and rural teachers, doctors andadministrator working women with regard to their mental health and maritalsatisfaction.